The importance of early identification of infusion-related reactions to monoclonal antibodies - Cáceres MC; Guerrero-Martín J; Pérez-Civantos D; Palomo-López P; Delgado-Mingorance JI; Durán-Gómez N (Dove Medical Press, 2019)
Macarena C Cáceres,1 Jorge Guerrero-Martín,1 Demetrio Pérez-Civantos,2,3 Patricia Palomo-López,1 Juan Ignacio Delgado-Mingorance,4 Noelia Durán-Gómez11Department of Nursing, University of Extremadura, Badajoz, Spain; 2Department of Biomedicine, University of Extremadura, Badajoz, Spain; 3Intensive Care Medicine Department, University Hospital of Badajoz, Servicio Extremeño de Salud, Badajoz, Spain; 4Oncology Department, University Hospital of Badajoz, Servicio Extremeño de Salud, Badajoz, SpainAbstract: Monoclonal antibodies constitute important and useful tools in clinical practice and biotechnology for diagnosing and treating infectious, inflammatory, immunological and neoplastic diseases. This article reviews evidence on the different acute adverse effects of monoclonal antibodies, specifically infusion-related reactions (IRRs), and on the measures that should be taken before and during crises. A literature search using key terms relating to IRRs produced by monoclonal antibodies was undertaken to generate a comprehensive narrative review of the information available. Immunomodulatory monoclonal antibodies may produce IRRs and hypersensitivity-related reactions. Strategies to avoid or minimize the appearance of IRRs depend on the monoclonal antibody and type of patient and reaction (pre-medication, slowing infusion rates, infusion interruption or desensitization, etc.). Considering the great number of available monoclonal antibodies in current practice and those which will soon be authorized, it is mandatory to have clear guidelines that can give support to practitioners and nurses to help them respond quickly and safely to the different IRRs related to the use of these therapeutic drugs.Keywords: antibodies, monoclonal, drug-related side effects and adverse reactions, nurse practitioners